Analysis of mobile applications for learning around electronics in Mexico - Aguilar Juárez, Irene (2025)
The purpose of this research was to explore educational mobile applications of electronics in Spanish to identify those that favor the learning of university students, specifically from the Computer Engineering degree program at the UAEM Texcoco University Center. An evaluation instrument was developed based on technical and didactic criteria based on the constructivist model, prioritizing interactivity, usability, educational content and feedback. The methodology included a literature review on evaluation instruments and the use of mobile applications as self-directed learning tools. The applications were selected through an analysis of their performance. Data were obtained from university students who applied the instrument. It was identified that the application “Electrician’s Manual” was the best rated in its didactic properties with 9.33 points, “Electrodoc” was placed with the lowest score with 8.14. In the technical evaluation also “Electrician’s Manual” was the best rated with 9.08 points and ‘CircuitJam’ obtained the lowest score (6.94), however, it was identified that “CircuitJam” is a didactic game whose properties do not match the properties of non-playful PPPs, so it is necessary to develop specific evaluation instruments for serious games. Seven applications were also highlighted as the most effective, grouped into resource libraries, simulators and games. These tools showed potential to improve the understanding of complex electronics concepts, promoting active learning. The study includes recommendations for their integration in classrooms and suggests future research.